Toughened epoxy microsphere and preparation method thereof
By reacting the epoxy resin with the curing agent first to form a prepolymer and forming a blend system in the polyethylene glycol solvent, epoxy microspheres with regular shape were prepared, and the problem of insufficient toughness and strength of the existing epoxy resin materials was solved, and the effect of improving the mechanical properties of epoxy was achieved.
Patent Information
- Application Number
- CN202411944625.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-21
AI Technical Summary
Due to the high curing density of existing epoxy resin materials, the body toughness and strength are low, making it difficult to meet the needs of toughening and strengthening.
By first reacting the epoxy resin with the curing agent to form a low molecular weight prepolymer, and forming an epoxy/PPG binary blend system in the polyethylene glycol solvent, as the curing reaction proceeds, the molecular weight of the epoxy increases and finally precipitates out in the shape of a ball. In this method, the molar excess of the curing agent is 20%, and the number average molecular weight of the polyether solvent is between 600 and 2000.
A regular-shaped epoxy microspheres were prepared, with a high glass transition temperature of about 170°C, and the epoxy microspheres were imparted with reactivity by excessive curing agent, enhancing the interface compatibility between the microspheres and the matrix, thereby improving the mechanical properties of the epoxy.
Smart Images

Figure CN119661875A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of toughened epoxy microspheres, and more particularly to toughened epoxy microspheres and a preparation method thereof. Background Art
[0002] Polymer microspheres are widely used in many aspects such as chromatography packaging materials, colloidal crystals, particle additives and templates for porous materials. For example, microspheres such as polymethyl methacrylate (PMMA) and polystyrene (PS) are mainly formed by precipitation polymerization of vinyl monomers and their crosslinkers. However, due to the low glass transition temperature and lack of solvent resistance of PMMA and PS thermoplastic microspheres, their application range is severely limited. However, thermosetting epoxy microspheres have many advantages in terms of heat resistance and chemical inertness, and are also low in price, so they have certain advantages in terms of application.
[0003] Epoxy resin polymer materials have excellent mechanical properties, chemical inertness, electrical insulation, light weight and low cost. They are ideal electronic packaging materials and are widely used in the field of microelectronic integration. However, epoxy resin materials have high curing density, resulting in low body toughness and strength. Therefore, how to toughen and strengthen epoxy resin has always been a research hotspot in the industry. Therefore, improving the toughness and strength of epoxy-based composite materials has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0004] In view of the above-mentioned defects of the prior art, the present invention provides a toughened epoxy microsphere and a preparation method thereof.
[0005] The technical solution adopted by the present invention to solve the technical problem is: to provide a toughened epoxy microsphere, and the raw materials for preparing the toughened epoxy microsphere include the following components in parts by mass:
[0006] Epoxy resin 100 parts
[0007] Curing agent 31-37.2 parts
[0008] Polyether solvent 65.5-524 parts.
[0009] In the toughened epoxy microspheres of the present invention, the epoxy resin is bisphenol A type epoxy resin.
[0010] In the toughened epoxy microspheres of the present invention, the curing agent is an aromatic diamine high temperature curing agent.
[0011] In the toughened epoxy microspheres of the present invention, the polyether solvent is polyethylene glycol.
[0012] In the toughened epoxy microspheres of the present invention, the mass ratio of the prepolymer formed by the epoxy resin and the curing agent to the polyether solvent is less than or equal to 1:4.
[0013] In the toughened epoxy microspheres of the present invention, the curing agent has a molar excess of 20%.
[0014] In the toughened epoxy microspheres of the present invention, the number average molecular weight of the polyether solvent is between 600-2000.
[0015] Another technical solution adopted by the present invention to solve the technical problem is: to provide a method for preparing toughened epoxy microspheres, the preparation method comprising the following steps:
[0016] S101, weighing epoxy resin and curing agent according to the mass ratio, placing them on a constant temperature hot plate preheated to 140° C., and magnetically stirring for 10 minutes to completely dissolve the curing agent in the epoxy resin to form an epoxy curing agent prepolymer;
[0017] S102, continue to add the polyether solvent into the heating container, and continue magnetic stirring on the hot plate at 120° C. for 5 minutes to completely dissolve the epoxy curing agent prepolymer in the polyether solvent.
[0018] In the preparation method of the present invention, the method further comprises:
[0019] S103, placing the dissolved sample in a constant temperature oven at 150° C. for a reaction time of 10 hours. After the reaction is completed, the obtained sample is washed several times with hot ethanol to remove the polyether solvent, and the precipitate is dried to obtain toughened epoxy microspheres.
[0020] In the preparation method of the present invention, the mass ratio of the prepolymer formed by the epoxy resin and the curing agent to the polyether solvent is less than or equal to 1:4, the curing agent has a molar excess of 20%, and the number average molecular weight of the polyether solvent is between 600-2000.
[0021] The implementation of the toughened epoxy microspheres and the preparation method thereof of the present invention has the following beneficial effects: the present invention first reacts the epoxy resin with the curing agent to form a low molecular weight prepolymer, and then disperses it in a polyethylene glycol (PPG) solvent with a certain molecular weight to form an epoxy / PPG binary blend system. As the curing reaction proceeds, the molecular weight of epoxy increases continuously, and eventually precipitates from the polyethylene glycol solvent in the shape of a ball. The present invention only requires a simple process to prepare epoxy microspheres with regular shapes, and the glass transition temperature (Tg) thereof is relatively high, about 170°C; the excess curing agent gives the epoxy microspheres a certain reactivity, which can react with the epoxy matrix to play a toughening and strengthening role, thereby enhancing the interface compatibility between the microspheres and the matrix, thereby improving the mechanical properties of the epoxy. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention will be further described below with reference to the accompanying drawings and embodiments, in which:
[0023] Figure 1 It is a schematic diagram of the structure of the experimental light scattering device in the present invention;
[0024] Figure 2 is a schematic diagram of the final phase structure of the prepolymer and polyethylene glycol blend in the present invention;
[0025] Figure 3 Schematic diagram of the phase separation behavior of the S21 system isothermally cured at 150° C. in the present invention;
[0026] Figure 4 is a schematic diagram of the phase separation behavior of the S11 system isothermally cured at 150° C. in the present invention;
[0027] Figure 5 Schematic diagram of the phase separation behavior of the S12 system isothermally cured at 150° C. in the present invention;
[0028] Figure 6 Schematic diagram of the phase separation behavior of the S14 system during isothermal curing at 150° C. in the present invention;
[0029] Figure 7 Schematic diagram of light scattering curves of different ratios of prepolymer and polyethylene glycol systems isothermally cured at 150° C. in the present invention;
[0030] Figure 8 is a relationship diagram between qm and t of the isothermal curing of the prepolymer and polyethylene glycol binary system at 150° C. in the present invention;
[0031] Fig. 9 is a schematic diagram of the morphology of epoxy microspheres under OM and SEM in the present invention;
[0032] Fig.10 It is the infrared spectrum of epoxy microspheres and DGEBA monomers in the present invention, and the schematic diagram of DSC curves of the reactions of different epoxy microspheres with DGEBA;
[0033] Fig.11 It is a secondary scanning DSC curve of epoxy microspheres and bulk epoxy resin in the present invention, and a schematic diagram of thermogravimetric analysis curve of epoxy microspheres and bulk epoxy resin.
[0034] Fig.12 It is a schematic diagram of the process of preparing toughened epoxy microspheres. DETAILED DESCRIPTION
[0035] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0036] The present invention is further described below in conjunction with the examples and comparative examples. Except for the homemade epoxy microspheres, all other raw materials involved in the present application can be purchased on the market.
[0037] Example 1
[0038] The invention discloses a preparation method for epoxy microspheres, comprising the following components by weight: 100 parts of epoxy resin, 31 parts of curing agent and 524 parts of solvent.
[0039] The epoxy resin is bisphenol A epoxy resin;
[0040] The curing agent is 4,4-diaminodiphenyl sulfone;
[0041] The solvent is polyethylene glycol PPG, with a number average molecular weight of about 1000 (PPG-1000);
[0042] The preparation method of the above-mentioned epoxy microspheres is as follows:
[0043] Weigh the epoxy resin and curing agent in a beaker, put them on a constant temperature hot plate preheated to 140°C, and stir them magnetically for 10 minutes to completely dissolve the curing agent in the epoxy resin; then add PPG-1000 to the beaker, and continue to stir magnetically for 5 minutes on a hot plate at 120°C to completely dissolve the epoxy / curing agent prepolymer in PPG-1000. Put another part of the sample in a constant temperature oven at 150°C for reaction, and the reaction time is set to 10 hours. After the reaction is completed, the obtained sample is washed several times with hot ethanol to remove PPG-1000, and the precipitate is dried to finally obtain a light yellow powder, namely epoxy microspheres.
[0044] Example 2
[0045] The difference between this embodiment and embodiment 1 is that the contents of the components are as follows: 100 parts of epoxy resin, 37.2 parts of curing agent, and 524 parts of solvent.
[0046] Example 3
[0047] The difference between this embodiment and embodiment 1 is that the contents of the components are as follows: 100 parts of epoxy resin, 31 parts of curing agent, and 65.5 parts of solvent.
[0048] Example 4
[0049] The difference between this embodiment and embodiment 1 is that the contents of the components are as follows: 100 parts of epoxy resin, 31 parts of curing agent, and 131 parts of solvent.
[0050] Example 5
[0051] The difference between this embodiment and embodiment 1 is that the contents of the components are as follows: 100 parts of epoxy resin, 31 parts of curing agent, and 262 parts of solvent.
[0052] Example 6
[0053] Preparation of an epoxy material, the content of each component is as follows: 100 parts of epoxy resin, 31 parts of curing agent. The preparation process is as follows: weigh the epoxy resin and curing agent in a beaker, put them on a constant temperature hot plate preheated to 140°C, and stir them magnetically for 10 minutes to completely dissolve the curing agent into the epoxy resin. Then pour it into an aluminum mold for curing, and the curing process is: pre-curing 150°C / 5h + post-curing 200°C / 2h.
[0054] Example 7
[0055] The difference between this embodiment and embodiment 6 is that the content of each component is as follows: 100 parts of epoxy resin, 31 parts of curing agent, and 10 parts of reactive epoxy microspheres.
[0056] Example 8
[0057] The difference between this embodiment and embodiment 6 is that the contents of the components are as follows: 100 parts of epoxy resin, 31 parts of curing agent, and 20 parts of reactive epoxy microspheres.
[0058] Example 9
[0059] The difference between this embodiment and embodiment 6 is that the contents of the components are as follows: 100 parts of epoxy resin, 31 parts of curing agent, and 20 parts of reactive epoxy microspheres.
[0060] The present invention first reacts epoxy resin and curing agent to form a low molecular weight prepolymer, and then disperses it in a polyethylene glycol (PPG) solvent with a certain molecular weight to form an epoxy / PPG binary blend system. As the curing reaction proceeds, the molecular weight of epoxy increases continuously, and finally precipitates from the polyethylene glycol solvent in the shape of a ball. The present invention only requires a simple process to prepare epoxy microspheres with regular shapes, and the glass transition temperature (Tg) thereof is relatively high, about 170°C; the excess curing agent gives the epoxy microspheres a certain reactivity, which can react with the epoxy matrix to play a role of toughening and strengthening, thereby enhancing the interface compatibility between the microspheres and the matrix, thereby improving the mechanical properties of the epoxy.
[0061] Materials Characterization Methods
[0062] Optical Microscopy (OM)
[0063] The optical microscope model used in the present invention is SPL-50TF, the microscope magnification is selected as 100, and it is equipped with a precise constant temperature heating table. The specific process is as follows: place two glass sheets on the heating table, take out the uncured sample refrigerated in the refrigerator, drop an appropriate amount of the sample in the center of one of the glass sheets, cover it with another glass sheet, and use tweezers to squeeze the sample into a thin film while squeezing out the air that may be contained in the sample as much as possible. Then place the glass sheet on a constant temperature heating table preset to 150°C perpendicular to the lens, and start capturing images immediately, and stop shooting when the phase structure is fixed. The phase separation process of different systems is analyzed by reading the time interval of the photos.
[0064] Time-Resolved Light Scattering (TRLS)
[0065] The main components of the homemade time-resolved light scattering instrument are as follows: a helium-neon laser emitting red laser with a wavelength of 632.8nm, a precision constant temperature heating stage and a digital camera. Since different systems may follow different phase separation mechanisms when phase separation occurs, TRLS can analyze and track the phase separation process of the sample by capturing the changes in the scattered light intensity caused by the fluctuations in the concentration of the components in the sample during the phase separation process. The sample preparation in the TRLS experiment is the same as the method used in the OM experiment, and then the sample is placed in the center of the 150℃ constant temperature heating stage. There is a camera above the heating stage and a helium-neon laser below. The laser passes through the sample on the heating stage and is captured by the camera. The time interval for collecting data is set, and the system will record the changes in the scattered light intensity during the phase separation process according to the set time interval until the position of the scattering peak and the maximum intensity of the scattered light remain unchanged. Figure 1 A schematic diagram of the light scattering setup for this experiment is shown.
[0066] Fourier Transform Infrared Spectrometer (FT-IR)
[0067] The reactive groups of epoxy microspheres were characterized and analyzed using a Nicolet AVATAR 370 Fourier transform infrared spectrometer. Sample preparation: Take a small amount of epoxy microspheres and dry them under an infrared lamp. Mix the completely dried epoxy microspheres with spectrally pure potassium bromide at a mass ratio of 1:200, and grind the mixture in a mortar for 2 to 3 minutes to mix the samples evenly. Take an appropriate amount of sample and press it into a uniform sheet. Place it under an infrared lamp and bake it for 1 minute to prevent potassium bromide from absorbing moisture and affecting the test results. Finally, place the sheet in the instrument for testing.
[0068] Differential Scanning Calorimetry (DSC)
[0069] The main uses of DSC in this experiment are: 1. Determine the Tg of epoxy microspheres and bulk epoxy resin; 2. Detect whether the synthesized reactive epoxy microspheres react chemically with the DGEBA monomer (whether an enthalpy change occurs).
[0070] The test conditions of Tg of epoxy resin and epoxy microspheres are as follows: the mass of the sample is about 5 mg, the heating rate is 10℃ / min, the temperature range of the experiment is 30℃-250℃, and the test is carried out in a dry nitrogen environment. The first heating eliminates the thermal history, and the data measured by the second heating is processed and recorded as the Tg of the sample.
[0071] The test conditions for whether the reaction of reactive epoxy microspheres with DGEBA monomer generates reaction heat are as follows: about 1 mg of reactive epoxy microspheres, about 4 mg of DGEBA monomer, a heating rate of 10°C / min, a temperature range of 30°C-350°C, and the test is carried out in a dry nitrogen environment to observe whether there is an exothermic peak caused by the chemical reaction. At the same time, as a control group, the epoxy microspheres obtained in the same stoichiometric ratio reacted with the DGEBA monomer, and the test conditions were the same as above.
[0072] Thermogravimetric analysis (TGA)
[0073] In this experiment, the thermal stability of epoxy microspheres and bulk epoxy resin was characterized by using TA's TGA-55 thermogravimetric analyzer to understand the thermal decomposition temperature of epoxy microspheres and bulk epoxy resin, and to analyze the reasons for the difference in thermal decomposition temperature. The test conditions are as follows: the sample mass is about 5 mg, the heating rate is 10℃ / min, the temperature range of the experiment is 30℃-800℃, and the test is carried out in a dry nitrogen environment.
[0074] Scanning electron microscopy (SEM)
[0075] The morphology of epoxy microspheres was observed using Hitachi S-3400 SEM. Sample preparation: A small amount of epoxy microspheres were dispersed in anhydrous ethanol and subjected to ultrasonic oscillation to form a relatively uniform suspension. The suspension was absorbed onto copper foil and dried in an oven before the sample surface was sprayed with gold.
[0076] Figure 2 The final phase structures of Epoxy / PPG-1000 blends: S21(a), S11(b), S12(c) and S14(d).
[0077] OM was used to observe the final phase structures of four systems with different mass ratios of DGEBA and PPG-1000 (mass ratios of epoxy resin + curing agent / PPG are 2:1, 1:1, 1:2, and 1:4, respectively referred to as S21, S11, S12, and S14) after phase separation. It can be seen that the phase structures formed by the above four systems after phase separation are significantly different. S21 system ( Figure 2 -a) is an epoxy-rich phase and a PPG-rich phase intertwined to form a dual continuous phase structure, in which i represents an epoxy-rich phase and ii represents a PPG-rich phase. For the S11 system, the epoxy-rich phase is dispersed in the PPG continuous phase, and the epoxy-rich phases cannot be connected to each other to form a continuous phase. The phase structure of the S12 system is similar to that of the S11 system, in that both epoxy-rich phases are dispersed in the PPG continuous phase. However, unlike the S11 system, the size of the epoxy-rich phase in the S12 system is significantly smaller than the size of the epoxy phase in the S11 system. The phase structure formed by the S14 system is significantly different from the previous three systems, and the epoxy-rich phase is dispersed in the PPG continuous phase as spherical particles. The main reason for the difference in the phase structure of the four systems is the different content of DGEBA in the system. For the S21 system, the mass ratio of DGEBA+DDS to PPG-1000 is 2:1, and the epoxy prepolymer content in the system is relatively high. When phase separation occurs, the epoxy phase slowly coarsens and then connects together to form a continuous epoxy phase. As for the S11 and S12 systems, the DGEBA content in the system is lower than that in the S21 system. When phase separation occurs, it is difficult for the epoxy phase to connect with each other to form a continuous phase, and finally a structure is formed in which the epoxy-rich phase is dispersed in the PPG continuous phase. Since the DGEBA content of the S11 system is higher than that of the S12 system, in the final phase structure, the size of the epoxy-rich phase of the S11 system is significantly larger than that of the epoxy phase in the S12 system. Compared with the S12 system, the DGEBA content in the S14 system is further reduced. After a long period of curing reaction, the epoxy phase is separated from the PPG phase in the form of spherical particles.
[0078] refer to Figure 3 Schematic diagram of the phase separation behavior of the S21 system during isothermal curing at 150°C. When the proportion of the two components of the blend formed by epoxy resin and thermoplastic resin is appropriate, the phase separation follows the reaction-induced phase separation mechanism (RIPS), that is, as the curing reaction proceeds, the molecular weight of the epoxy prepolymer increases, causing the solubility parameters of the epoxy phase and the thermoplastic phase to mismatch, resulting in the phenomenon of two-phase separation. This experiment used an optical microscope to track and record the phase structure evolution of the above four systems when phase separation occurred. Figure 3 The phase structure changes of the S21 system during isothermal curing at 150°C were recorded.
[0079] In the early stage of curing reaction, the mixture is in a homogeneous state, indicating that the epoxy prepolymer and PPG-1000 have good compatibility and no phase separation occurs between the two phases ( Figure 3 -a). Afterwards, as the curing reaction proceeds, the molecular weight of the epoxy prepolymer continues to increase, resulting in the solubility parameters between the epoxy phase and the PPG phase no longer matching, and phase separation occurs at 287s. At this time, the system generally presents a micro-bicontinuous phase structure ( Figure 3 -b). Then, at 293s ( Figure 3 -c), the epoxy-rich phase gradually becomes larger and coarser, and the system temporarily presents a phase-inverted structure (the component with a higher content in the system is the dispersed phase, and the component with a lower content is the continuous phase). Then, at 302s, the epoxy-rich phases connect to form a continuous phase, and finally form a dual-continuous phase structure ( Figure 3 -d). Then, as the curing reaction proceeds, the epoxy resin gels to form a three-dimensional cross-linked network with a fixed phase structure. The above tracking dynamic process shows that the S21 system follows the spinodal decomposition (SD) mechanism when reaction-induced phase separation occurs. Figure 3 -c, 3-d, the formation of secondary phase separation of epoxy / PPG blends was observed, where the epoxy-rich phase contained the PPG dispersed phase, and the PPG-rich phase contained the epoxy dispersed phase. This is because during the phase separation process, the fast-moving epoxy phase will be restricted by the slow-moving PPG phase, and this part of the epoxy prepolymer undergoes cross-linking reaction in the PPG phase. When the local concentration in the system reaches a dynamic equilibrium, secondary phase separation will occur.
[0080] refer to Figure 4 Schematic diagram of the phase separation behavior of the S11 system during isothermal curing at 150°C. Similarly, the phase separation behavior of the S11 system was tracked by OM. Figure 4 As shown, the binary blend is in a homogeneous state at the initial stage of the curing reaction ( Figure 4 a). As the curing reaction proceeds, at 455s, the epoxy phase and the PPG phase begin to separate. However, the S11 system does not present a microbicontinuous structure similar to the S21 system, but rather a very small epoxy-rich phase dispersed in a continuous PPG-rich phase ( Figure 4 b). Then at 660s, the epoxy-rich phase continues to coarsen and grow in size ( Figure 4 c). Then, at 965s, the size of the epoxy-rich phase becomes larger and larger, and finally forms a dispersed phase structure ( Figure 4 d). After that, the curing reaction continues to gel the epoxy resin and fix the phase structure. It is worth noting that the dynamic phase separation behavior of the S11 system shows significant differences from that of the S21 system, belonging to the nucleation and growth (NG) mechanism.
[0081] refer to Figure 5 Schematic diagram of the phase separation behavior of the S12 system during isothermal curing at 150 °C. Figure 5 The phase separation process of the S12 system is shown. Its dynamic phase separation behavior is similar to that of the S11 system. The epoxy-rich phase continues to coarsen during the phase separation process, but is always distributed as an independent dispersed phase in the continuous phase of PPG. As the epoxy resin gels, it eventually presents a dispersed phase structure. However, unlike the S11 system, the size of the epoxy-rich phase in the final phase structure of the S12 system is significantly smaller than that of the S11 system.
[0082] refer to Figure 6 Schematic diagram of the phase separation behavior of the S14 system during isothermal curing at 150°C. For the S14 system, the content of DGEBA in the blend is much lower than that of the S21 system, and the dynamic phase separation behavior it exhibits is completely different, but similar to that of the S11 and S12 systems. Figure 6 The phase separation process of the S14 system is shown. Figure 6 a Figure 6 During the process of step b, the epoxy-rich phase precipitates from the PPG-rich phase in the form of particles to form a "core". Then at 1320s, since the epoxy concentration in the PPG phase is higher than the epoxy concentration around the "core", the epoxy in the PPG phase diffuses toward the lower concentration along the concentration gradient (i.e., diffuses toward the "core"). When the epoxy molecules enter the core area, the volume of the "core" increases, that is, the size of the epoxy particles continues to increase ( Figure 6 c). Then at 1840s, the epoxy particles continued to grow, and when the phase composition of the epoxy particles and the phase composition of its surroundings were in dynamic equilibrium, the phase separation ended. At this time, the epoxy particles showed an obvious microsphere structure, and the system finally showed a dispersed phase structure ( Figure 6 d).
[0083] Figure 7 Light scattering curves of isothermal curing of Epoxy / PPG systems with different ratios at 150°C. S21(a), S11(b), S12(c), S14(d).
[0084] In order to further determine the phase separation behavior of the epoxy / PPG binary system and the formation mechanism of epoxy microspheres, this experiment used a homemade TRLS instrument to in situ track the phase separation process of the epoxy / PPG binary system under isothermal curing at 150°C for semi-quantitative research.
[0085] Figure 7 The following are the time-varying curves of the scattered light intensity I and the scattered wave vector q of four systems with different epoxy / PPG ratios. The scattered wave vector (q) is a function of the wavelength (λ) and the scattering angle (θ), and the scattered wave vector (q) is defined by formula 1:
[0086]
[0087] The laser wavelength (λ) used in this experiment is 632.8nm.
[0088] from Figure 7 It can be seen that no scattering peak was observed in the four systems at the initial stage of curing, indicating that the system was homogeneous. After a period of induction, as the molecular weight of the epoxy prepolymer increased, the entropy of the system decreased, ΔG>0, the system phase separated, and a scattering peak could be observed. As the curing reaction proceeded, the two phases continued to separate, and the scattered light intensity (I) of the above four systems increased. For the S21 system, scattering began to appear after an induction period of 311s, and the peak value qm of its scattering wave vector decreased rapidly until it remained unchanged, indicating the end of the phase structure evolution. However, for the S11, S12, and S14 systems, scattering appeared later, at 485s, 655s, and 880s, respectively, the peak value qm of the scattering wave vector remained almost unchanged, and the scattered light intensity continued to increase. The TRLS monitoring results show that the phase separation mechanism of the S21 system follows the SD mechanism, while the phase structure evolution of the other three systems follows the NG mechanism.
[0089] In the actual experimental synthesis process, since it is difficult to obtain dispersed epoxy microspheres in systems with fewer PPG components (S21, S11, S12), this experiment selected the S14 system to prepare epoxy microspheres. The periodic distance Λm can be calculated according to the scattering vector qm by formula 2:
[0090]
[0091] Depend on Figure 8 It is known that qm is about 2.5 μm-1, corresponding to a diameter of the epoxy microsphere of about 2.5 μm.
[0092] Figure 8 The relationship diagrams of qm and t of the Epoxy / PPG binary system isothermally cured at 150°C, S21(a), S11(b), S12(c), and S14(d).
[0093] Tables 1 and 2 list the specific results of OM and TRLS tracking the phase separation of epoxy / PPG binary system, respectively.
[0094] Table 1 Results of OM tracking phase separation
[0095]
[0096] Table 2 Results of TRLS tracking phase separation
[0097]
[0098] From the OM tracking data in Table 1, the following conclusions can be drawn: 1. The time when the epoxy / PPG binary blend phase separation starts is delayed as the DGEBA content in the system decreases (287s for the S21 system, 455s for the S11 system, 585s for the S12 system, and 940s for the S14 system); 2. The evolution time of the epoxy / PPG binary blend phase separation increases as the DGEBA content in the system decreases (phase evolution time of the system: 15s for the S21 system, 510s for the S11 system, 785s for the S12 system, and 900s for the S14 system). Similarly, almost identical results were obtained by TRLS in Table 2. Compared with the other three systems, the phase structure evolution time of the S21 system is very short. This is because the S21 system is a phase separation process based on the SD mechanism. The main driving force of the phase separation is the concentration fluctuation between the components in the system, and its development process is very rapid. The other three systems are phase structure evolutions based on the NG mechanism, and the phase separation process is relatively slow.
[0099] Fig. 9 The morphology of epoxy microspheres under OM (a) and SEM (b). Fig. 9 In a, we dispersed the obtained epoxy microspheres in DGEBA monomer for observation. It can be found that the epoxy microspheres are dispersed very evenly in DGEBA, and the epoxy microspheres do not agglomerate, which indicates that the epoxy microspheres have good compatibility with DGEBA. Fig. 9 b is the SEM photo of the epoxy microspheres obtained, which shows that the surface of the synthesized epoxy particles is smooth and has no obvious defects, and is a relatively perfect spherical structure. In addition, the epoxy microspheres have a certain size distribution, and the size of most epoxy microspheres is between 5 and 15 μm. The morphology of the epoxy microspheres obtained by OM and SEM is consistent.
[0100] Fig.10 Infrared spectra of epoxy microspheres and DGEBA monomer (a), and DSC curves of the reaction of different epoxy microspheres with DGEBA (b).
[0101] Two types of epoxy microspheres were prepared by precipitation polymerization in the S14 system by adjusting the dosage of the curing agent DDS, one with an equimolar ratio of DGEBA and DDS (mass ratio 100:31) and the other with a 20% molar excess of DDS (mass ratio 100:37.2) to ensure complete reaction of the epoxy monomer and excess amino groups on the surface of the epoxy microspheres. Fig.10 This is the result of characterizing the "reactivity" of epoxy microspheres. Fig.10 a shows the infrared spectrum of epoxy microspheres prepared with 20% excess DDS and the infrared spectrum of DGEBA monomer.
[0102] For epoxy microspheres, 3362cm-1 corresponds to the stretching vibration of HNH, 1591cm-1 corresponds to the bending vibration of NH, and 2880cm-1 corresponds to the stretching vibration of -CH2-. For DGEBA monomer, the weak broad peak at 3400cm-1 corresponds to the characteristic of -OH in the structure, and the sharp strong peak at 905cm-1 corresponds to the large number of epoxy groups in the DGEBA structure, while epoxy microspheres do not have any characteristic peaks here, which indicates that the epoxy groups have been completely reacted in the curing reaction.
[0103] In order to further explore the "reactivity" of epoxy microspheres given by excess curing agent, the reaction of epoxy microspheres generated by equal stoichiometric ratio and epoxy microspheres generated by 20% excess DDS with DGEBA was compared by DSC test. The results showed that Fig.10 b. For the red curve with equal stoichiometric ratio, there is no exothermic peak in the entire test range, indicating that there is no chemical reaction between the epoxy microspheres and DGEBA. For the black curve with 20% excess DDS, an obvious exothermic peak appears at 250℃-300℃, indicating that the epoxy microspheres and DGEBA do react chemically, which proves the existence of excess amino groups on the surface of the epoxy microspheres. FT-IR proves the existence of amino groups on the surface of epoxy microspheres, while DSC proves that epoxy microspheres with amino groups on the surface can indeed undergo a curing reaction with DGEBA. The results of FT-IR and DSC show that excess DDS curing agent can indeed give the epoxy microspheres a certain "reactivity", and this "reactivity" will improve the compatibility of the epoxy microspheres with the matrix.
[0104] Fig.11 The secondary scanning DSC curve of epoxy microspheres and bulk epoxy resin (a) and the thermogravimetric analysis curve of epoxy microspheres and bulk epoxy resin (b) are shown.
[0105] In addition to characterizing the morphology and reactivity of epoxy microspheres, the thermal properties were also tested and compared to determine the difference in Tg and thermal stability between epoxy microspheres generated by 20% excess DDS and bulk epoxy resin cured with an equivalent amount. The test results show that Fig.11 .
[0106] Fig.11a shows that the Tg of epoxy microspheres is about 170.0℃, and the Tg of bulk epoxy resin is about 205.5℃. Although the same monomer and curing agent are used, the Tg of epoxy microspheres is about 35℃ lower than that of bulk epoxy resin. Possible reasons are: 1. At the end of phase separation, the composition of epoxy microspheres is in equilibrium with the surrounding PPG phase, that is, PPG may remain in the epoxy microspheres, which will reduce the Tg of epoxy microspheres; 2. Epoxy microspheres are made with excess curing agent, and excess curing agent may plasticize the epoxy microspheres, thereby reducing the Tg of epoxy microspheres.
[0107] Fig.11 b is the thermogravimetric analysis curve of epoxy microspheres and bulk epoxy resin, in which the inserted figure is an enlarged view of the temperature range of 340℃-400℃. Generally speaking, the temperature (T95wt%) at which the polymer temperature rises and causes a loss of 5wt% due to thermal decomposition is often used to represent the thermal stability of the polymer. For bulk epoxy resin, T95wt% is about 394.3℃, while T95wt% of epoxy microspheres is about 359.8℃. This is because PPG exists in the composition of epoxy microspheres, and the boiling point of PPG-1000 is about 234.2℃. Therefore, when the temperature rises, PPG-1000 will decompose before epoxy, resulting in a lower T95wt% of epoxy microspheres, but there is not much difference between the main weight loss temperatures of epoxy microspheres and bulk epoxy resins (410.9℃ and 413.2℃, respectively).
[0108] Table 3 Effects of different epoxy microsphere contents on toughening and strengthening of epoxy matrix
[0109]
[0110] At the same time, the present invention also tests the effect of different contents of reactive epoxy microspheres (ESs) on the mechanical properties of epoxy, and the data are shown in Table 3. Among them, Neat EP is cured by DGEBA and DDS; EP / xESs is cured by DGEBA, DDS, and ESs, where x represents the content of ESs. It can be seen that the tensile strength, elongation at break and shear strength of the cured epoxy are significantly improved. This may be because the excess curing agent gives the epoxy microspheres "reactivity", which enhances the interfacial compatibility between the microspheres and the matrix, thereby improving the mechanical properties of the epoxy.
[0111] like Fig.12 FIG. 1 is a flow chart of a method for preparing toughened epoxy microspheres of the present invention. This embodiment discloses a method for preparing toughened epoxy microspheres, and the preparation method comprises the following steps:
[0112] S101, weighing epoxy resin and curing agent according to the mass ratio, placing them on a constant temperature hot plate preheated to 140° C., and magnetically stirring for 10 minutes to completely dissolve the curing agent in the epoxy resin to form an epoxy curing agent prepolymer;
[0113] S102, continue to add the polyether solvent into the heating container, and continue magnetic stirring on the hot plate at 120° C. for 5 minutes to completely dissolve the epoxy curing agent prepolymer in the polyether solvent.
[0114] Furthermore, the method also includes:
[0115] S103, placing the dissolved sample in a constant temperature oven at 150° C. for a reaction time of 10 hours. After the reaction is completed, the obtained sample is washed several times with hot ethanol to remove the polyether solvent, and the precipitate is dried to obtain toughened epoxy microspheres.
[0116] Preferably, the mass ratio of the prepolymer formed by the epoxy resin and the curing agent to the polyether solvent is less than or equal to 1:4, the molar excess of the curing agent is 20%, and the number average molecular weight of the polyether solvent is between 600-2000.
[0117] In addition, in the present invention, unless otherwise clearly specified and limited, the terms "connected", "connected", "stacked" and the like should be understood in a broad sense, for example, it can be fixedly connected, detachably connected, or integrated; it can be directly connected, or indirectly connected through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0118] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A toughened epoxy microsphere, characterized in that: The raw materials for preparing the toughened epoxy microspheres include the following components in parts by mass: Epoxy resin 100 parts Curing agent 31-37.2 parts Polyether solvent 65.5-524 parts.
2. The toughened epoxy microspheres according to claim 1, characterized in that: The epoxy resin is bisphenol A type epoxy resin.
3. The toughened epoxy microspheres according to claim 1, characterized in that: The curing agent is an aromatic diamine high temperature curing agent.
4. The toughened epoxy microspheres according to claim 1, characterized in that: The polyether solvent is polyethylene glycol.
5. The toughened epoxy microspheres according to claim 1, characterized in that: The mass ratio of the prepolymer formed by the epoxy resin and the curing agent to the polyether solvent is less than or equal to 1:
4.
6. The toughened epoxy microspheres according to claim 1, characterized in that: The curing agent has a molar excess of 20%.
7. The toughened epoxy microspheres according to claim 1, characterized in that: The number average molecular weight of the polyether solvent is between 600 and 2000.
8. A method for preparing toughened epoxy microspheres according to claim 1, characterized in that: The preparation method comprises the following steps: S101, weighing epoxy resin and curing agent according to the mass ratio, placing them on a constant temperature hot plate preheated to 140° C., and magnetically stirring for 10 minutes to completely dissolve the curing agent in the epoxy resin to form an epoxy curing agent prepolymer; S102, continue to add the polyether solvent into the heating container, and continue magnetic stirring on the hot plate at 120° C. for 5 minutes to completely dissolve the epoxy curing agent prepolymer in the polyether solvent.
9. The method for preparing toughened epoxy microspheres according to claim 8, characterized in that: After the step S102, the method further includes: S103, placing the dissolved sample in a constant temperature oven at 150° C. for a reaction time of 10 hours. After the reaction is completed, the obtained sample is washed several times with hot ethanol to remove the polyether solvent, and the precipitate is dried to obtain toughened epoxy microspheres.
10. The method for preparing toughened epoxy microspheres according to claim 8, characterized in that: The mass ratio of the prepolymer formed by the epoxy resin and the curing agent to the polyether solvent is less than or equal to 1:4, the curing agent has a molar excess of 20%, and the number average molecular weight of the polyether solvent is between 600-2000.
Citation Information
Cited By
Compression-resistant PET plastic bottle composite material and preparation method thereof
CN121991474A
A compression-resistant PET plastic bottle composite material and a preparation method thereof
CN121991474B